Independent study in Dentistry students’ - Baca, César (2022)
Introduction: Study or independent work is a strategy that students develop to achieve the proposed training objectives. Diverse countries consider independent study as counting inside of credits from the formative program. Material and methods: A transverse, descriptive, and observational study was carried out. The population was composed of 49 students enrolled in the Undergraduate Stomatology Program of the Universidad Peruana Cayetano Heredia, in the year 2021. The questionnaire in Google forms consisted of eleven questions and was sent by institutional email. The survey was validated (Cronbach’s alpha = 0.96). Results: 81.6% were women. The average hours that they dedicated to independent study between Monday and Friday was 3 hours (SD=1.4; Mín=1; Max=6) and on Saturdays and Sundays was 3.4 hours (SD = 1.4; Min = 0; Max = 7). 38.8% considered that the time they dedicated to independent study was not enough. As a regular activity, they spent 4.2 hours performing a case method and orthodontic laboratory activities, and as an occasional activity, they spent 8.4 hours on the portfolio. In the personal dimension, 71.4% had responsibilities at home, in the emotional dimension 65.3% experienced tension or stress, and in the physical dimension, 14,3% had health problems. 57.1% considered their study environment adequate and 81.6% considered that independent study was important. Conclusions: Independent study added to class activities involves ten hours of dedication by the fourth-year student, between Monday and Friday, which may represent an overload of hours that limits personal activities and responsibilities.